Tibial Shaft and Pilon Fractures With Associated Syndesmotic Injury: A Matched Cohort Assessment. Issue 3 (March 2022) - Purcell, Kevin F.; Bergin, Patrick F.; Russell, George V.; Graves, Matt L.; Jones, LaRita C.; Spitler, Clay A.
Abstract : Objective: To determine the outcomes of pilon and tibial shaft fractures with syndesmotic injuries compared with similar fractures without syndesmotic injury. Design: Retrospective case–control study. Setting: Level 1 trauma center. Patients/Participants: All patients over a 5-year period (2012–2017) with tibial shaft or pilon fractures with a concomitant syndesmotic injury and a control group without a syndesmotic injury matched for age, OTA/AO fracture classification, and Gustilo–Anderson open fracture classification. Intervention: Preoperative or intraoperative diagnosis of syndesmotic injury with reduction and fixation of both fracture and syndesmosis. Main Outcome Measurement: Rates of deep infection, nonunion, unplanned reoperation, and amputation in patients with a combined syndesmotic injury and tibial shaft or pilon fracture versus those without a syndesmotic injury. Results: A total of 30 patients, including 15 tibial shaft and 15 pilon fractures, were found to have associated syndesmotic injuries. The matched control group comprised 60 patients. The incidence of syndesmotic injury in all tibial shaft fractures was 2.3% and in all pilon fractures was 3.4%. The syndesmotic injury group had more neurologic injuries (23.3% vs. 8.3% P = 0.02), more vascular injuries not requiring repair (30% vs. 15%, P = 0.13), and a higher rate compartment syndrome (6.7% vs. 0%, P = 0.063). Segmental fibula fracture was significantly more common in patients with a syndesmotic injury (36.7% vs. 13.3%, P = 0.04). Fifty percent of the syndesmotic injury group underwent an unplanned reoperation with significantly more unplanned reoperations (50% vs. 27.5%, P = 0.04). The syndesmotic group had a significantly higher deep infection rate (26.7% vs. 8.3% P = 0.047) and higher rate of amputation (26.7% vs. 3.3% P = 0.002) while the nonunion rate was similar (17.4% vs. 16.7% P = 0.85). Conclusions: Although syndesmotic injuries with tibial shaft or pilon fractures are rare, they are a marker of a potentially limb-threatening injury. Limbs with this combined injury are at increased risk of deep infection, unplanned reoperation, and amputation. The presence of a segmental fibula fracture should raise clinical suspicion to evaluate for syndesmotic injury. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.